Extreme halophilic alcohol dehydrogenase mediated highly efficient syntheses of enantiopure aromatic alcohols - Alsafadi, Diya; Alsalman, Safaa; Paradisi, Francesca (Royal Society of Chemistry, 2017)
Enzymatic synthesis of enantiopure aromatic secondary alcohols (including substituted, heteroaromatic and bicyclic structures) were carried out using the halophilic alcohol dehydrogenase ADH2 from Haloferax volcanii (HvADH2). This enzyme showed an unprecedented substrate scope and absolute enatioselectivity. The cofactor NADPH was used catalytically and regenerated in-situ by the biocatalyst, in the presence of 5% ethanol. The efficiency of HvADH2 for conversion of aromatic ketones was markedly influenced by the steric and electronic factors as well as the solubility of ketones in the reaction medium. Furthermore, carbonyl stretching bands frequencies ν ( ) have been measured for different ketones to understand the effect of electron withdrawing or donating properties of the ketones substituents on the reaction rate catalyzed by HvADH2. Good correlation was observed between ν ( ) of methyl aryl-ketones and the reaction rate catalyzed by HvADH2. The enzyme catalyzed the reductions of ketone substrates on the preparative scale, demonstrating that HvADH2 would be a valuable biocatalyst for the preparation of chiral aromatic alcohols of pharmaceutical interest.